ANALISIS TOKOH PADA CERPEN â€œIBU PERGI KE LAUTâ€ MELALUI PENDEKATAN KRITIK MIMETIK SERTA RELEVANSINYA DENGAN PEMBELAJARAN SASTRA DI SEKOLAH DASAR - Heny Kusuma Widyaningrum (Universitas Ahmad Dahlan, 2018)
The objective of this study is to analyze the literary criticism through mimetic approach on short stories Ibu Pergi ke Laut by Puthut EA and explain the relevance with learning literature in Elementary school. This research is descriptive qualitative study. Data collection techniques used is book research, check out, and record. Data analysis technique used is the analysis of dialectical data. Novel Ibu Pergi ke Laut is based on the real story of tsunami in Aceh on December 26, 2004. Most of the data is similar to the data which the truth of the fact can be proved because the story is really happened and reflected the real experienced by either the victim or the family at that time. This short story can be used by the students as literature learning materials in primary schools which the story was taken from others' experience reflected how to face a problem in life.